Analysis of Factors Causing Pending BPJS Health Claims for Inpatients at Kartika Husada Setu Hospital in 2024 - Situmorang, Budi Asih; Aziz , Abdul; Hutapea, Fresley (IJBLE Scientific Publications Community Inc., 2025)
This study is motivated by the high number of pending BPJS Health claims at Kartika Husada Setu Hospital. Pending claims can disrupt the hospital’s cash flow and potentially reduce the quality of healthcare services. The purpose of this research is to identify the factors causing pending BPJS Health claims for inpatient services at Kartika Husada Setu Hospital in 2024. This study employs a qualitative research approach with a retrospective design. Data were collected through in-depth interviews, direct observations, and document analysis. The informants included the hospital director, finance manager, service manager, head of the medical records unit, casemix staff, coder, and heads of inpatient wards. The findings indicate that the primary cause of pending claims is the mismatch in medical indications, accounting for 73 files (79.4%), followed by incomplete documentation in 4 files (4.4%), and inaccurate coding in 15 files (16.2%). The mismatch in medical indications often involves unmet emergency and inpatient criteria, as well as a lack of therapeutic evidence. Incomplete documentation is frequently found in medical summaries, while inaccurate coding results from differing interpretations between the hospital and BPJS Health verifiers. The hospital needs to enhance training for staff involved in the BPJS claims process, optimize the use of electronic medical record systems, improve coordination with BPJS Health verifiers, and establish a quality and cost control team. The implementation of these recommendations is expected to reduce the number of pending claims, thereby improving operational efficiency and the quality of healthcare services provided to patients.